Relationship Between Knowledge and Attitude towards Children with Special Needs with Caring Behavior in FKIP UNS Students Who Take Inclusive Education Courses in 2020/2021 - Dita Mustika Sari; Munawir Yusuf; Supriyadi Supriyadi (Journal of Disability, 2022)
Abstract This study aims to determine whether or not there is a relationship between students' knowledge/understanding about ABK and caring behavior towards ABK, to determine whether or not there is a relationship between student attitudes and caring behavior towards ABK, and to determine whether or not there is a relationship between knowledge/understanding and attitudes on student caring behavior. The research method used is a quantitative method with a descriptive design. The sample in this study were students who took the 2020/2021 inclusive education courses selected with the cluster random sampling technique. Research data was collected using a questionnaire and then analyzed using multiple linear regression analysis. The results showed that there was a relationship between student knowledge/understanding and caring behavior for children with special needs, there was a relationship between attitude and caring behavior students towards children with special needs, and there is a relationship between knowledge/understanding and attitudes with caring behavior of students in children with special needsKeywords: Children with Special Needs; Knowledge/Understanding; Attitude; Behavior